Synthesis and Biological Evaluation of Some Dipeptide Derivatives and Their Heterocyclic Compounds - Basheer, Huda A.; Sabir, Sabir A.; Ibrahiem, Aveen A. (Science Journal of University of Zakho, 2015)
The protected dipeptide esters (3a-e, 4a-l) is prepared by the reaction of compounds (1a-e, 2a-d) with dicyclohexylcarbodiamide (as coupling reagent) and amino acid esters .Thereafter hydrazides (5a-e, 6a-j) are obtained by the reaction of corresponding esters with hydrazine hydrate. Hydrazones (7a-e, 8a-e) are synthesized by the reaction of the above hydrazides with p-nitro benzaldehyde , which was cyclized to 2,5- disubstituted 1,3,4- oxadiazole (9a-e, 10a-e) through lead oxide and to phthalazines (13a-b) through hydrochloric acid. 1,3,4- oxadiazole -2- thione (11a-b, 12a-e) were prepared by the reaction of the corresponding hydrazides with carbon disulfide in alcoholic potassium hydroxide. Hydrazides were reacted with ammonium thiocyanate to afford thiosemicarbazide (14a-c) which were cyclized to 1,2,4- triazole -3- thione (15a-b) in sodium hydroxide medium. The structures of the synthesized compounds were confirmed by physical and spectral methods. The antibacterial activity of the prepared compounds (5d, 7a, 9e, 10d, 11a, 12e, 13a, 14b) against the gram +ve and –gram –ve Bactria (Staphylococcus aureus, Bacillus subtilis, Escherichia coli and Proteus mirabilis) were studied and discussed